Recycled aggregate and preparation method thereof
By controlling the particle grading and adding fine gelling materials, combined with the use of limestone waste mud to supplement the fine pores, the problems of pores and microcracks on the surface of the regenerated aggregate are solved, and their compactness and strength are significantly improved, and the comprehensive performance of concrete is improved.
Patent Information
- Application Number
- CN202510008049.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The performance of existing regenerated aggregates is low, mainly because there are a large number of pores and micro-cracks on the surface and the uneven particle size, which leads to micro-cracks in the interface transition area with the cement slurry, affecting its comprehensive performance.
By controlling the particle grading, the content of harmful pores is reduced; fine gelled material particles are added to reduce the total specific surface area and water consumption of the material; use limestone-containing waste mud to supplement the fine pores. Limestone has the effect of reducing water, increasing the compactness of the system, and reducing the water-cement ratio and harmful pore content.
It significantly improves the compactness and strength of the recycled aggregate, reduces the water-cement ratio and harmful pore content, and improves its application performance in concrete.
Smart Images

Figure CN119797790A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a recycled aggregate and a preparation method thereof. Background Art
[0003] Recycled aggregate is a material made by crushing, screening and mixing construction waste in a certain proportion. It can be used to replace natural aggregate to prepare concrete with different performance and usage requirements. However, the large number of pores distributed on the surface of recycled aggregate leads to a large number of microcracks in the interface transition zone (ITZ) between aggregate and cement paste, and the crushing and screening process of waste concrete causes a large number of irregular edges and uneven particle size distribution in the recycled aggregate. For the above reasons, the quality and comprehensive performance of recycled aggregate are far inferior to natural aggregate. Therefore, exploring methods to improve the performance of recycled aggregate has become an urgent research topic for many scholars at home and abroad.
[0004] Since the main factors affecting the performance of recycled aggregates are the cement mortar adhered to the surface of the recycled aggregates and the old interface transition zone, the methods for strengthening recycled aggregates are mainly divided into three categories: removing old mortar, strengthening old mortar, and improving the mixing process of recycled concrete. The methods for removing old mortar mainly include mechanical grinding, heating grinding, acid treatment, etc. The mechanical grinding method uses the shear stress generated between the wall of the high-speed rotating eccentric gear and the surface of the recycled aggregate to remove the adhered mortar. The heating grinding method is to first pre-treat the recycled aggregate at high temperature to achieve the purpose of weakening the old mortar layer on its surface, and then mechanically grind it to better remove the old mortar. The acid treatment method is to soak the recycled aggregate in an acid solution to dissolve the old mortar on the surface of the aggregate to achieve the purpose of modifying the recycled aggregate. The methods for strengthening old mortar mainly include volcanic ash slurry immersion method, polymer emulsion immersion method, carbonization treatment method, etc. The pozzolan slurry soaking method is to add pozzolan mineral admixtures (such as fly ash, silica fume, slag, etc.) to pure cement slurry to prepare pozzolan slurry. The slurry can fill the pores and microcracks on the surface of the recycled aggregate and react with the attached mortar, thereby achieving the purpose of strengthening the recycled aggregate. The polymer emulsion soaking method is to prepare a modified solution with a certain proportion of polymer emulsion and soak the recycled aggregate in a vacuum pump. Among them, the commonly used polymer emulsion is polyvinyl alcohol (PVA) emulsion, which has gelling properties and can quickly solidify and fill the pores and microcracks on the surface of the attached old mortar, significantly reducing the water absorption rate and other properties of the recycled aggregate. The carbonization treatment method is to use CO2 to accelerate the carbonization of the old mortar on the surface of the recycled aggregate to generate calcium carbonate and silica gel, which effectively fills its internal pores and microcracks. Although the above methods have improved the quality and comprehensive performance of the recycled aggregate to a certain extent, there are still limitations such as complex process, serious energy consumption, and poor effect. Therefore, scholars at home and abroad have been looking for a modification technology that is simple in process, cost-saving and has significant effects. Summary of the invention
[0005] The present invention aims to solve the problems existing in the prior art and provides a recycled aggregate and a preparation method thereof. The invention realizes precise stacking by controlling the particle grading and reduces the harmful pore content. Fine cementitious material particles are added to reduce the total specific surface area of the material and reduce the water consumption. In addition, waste mud containing limestone is used to supplement the micropores. Limestone has a certain water-reducing effect, which can further increase the compactness of the system, reduce the water-cement ratio, and reduce the harmful pore content.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A recycled aggregate is made of the following raw materials in parts by weight: 40-50 parts of tailings, 2-5 parts of coal gangue, 5-10 parts of building phosphogypsum, 10-15 parts of strong electrolyte solvent, 4-6 parts of weak electrolyte solvent, 20-25 parts of steel slag, 5-8 parts of carbide slag, 1-3 parts of waste mud, 0.1-0.5 parts of carbon fiber, 2-4 parts of steel fiber and 0.5-1 part of water reducing agent.
[0008] Preferably, the tailings are one or more of iron tailings, graphite tailings, and copper tailings; the resistivity of the tailings is less than 1000 ohms, the fineness modulus of the tailings is 2.5-3.0, and the silicon content of the tailings is greater than 60%.
[0009] Preferably, the coal gangue is solid waste discharged during coal mining and coal washing, the particle size of the coal gangue is 0.1-2 mm, and the fineness modulus of the coal gangue is 3.3-3.5.
[0010] Preferably, the building phosphogypsum is obtained by heating and dehydrating solid waste phosphogypsum generated in the phosphoric acid production process, and its hemihydrate gypsum content is greater than 80%, and the 80um sieve residue is less than 10%.
[0011] Preferably, the strong electrolyte solvent is one or more of an aqueous solution of ferric sulfate, an aqueous solution of sodium sulfate, an aqueous solution of sodium hydroxide, and an aqueous solution of potassium hydroxide; and the mass fraction of the strong electrolyte solvent is 20-35wt%.
[0012] Preferably, the weak electrolyte solvent is one or more of an aqueous solution of ferric sulfate, an aqueous solution of sodium sulfate, an aqueous solution of sodium hydroxide, and an aqueous solution of potassium hydroxide; and the mass fraction of the weak electrolyte solvent is 2-5wt%.
[0013] Preferably, the calcium content of the steel slag is greater than 50%, and the specific surface area of the steel slag is 350-400m 2 / kg.
[0014] Preferably, the carbide slag is the main solid waste from carbide hydrolysis to produce acetylene gas, the calcium content of the carbide slag is greater than 80%, and the specific surface area of the carbide slag is 350-400m2 / kg.
[0015] Preferably, the waste mud is solid waste from water washing and powder removal in the limestone machine-made sand production process, the water content of the waste mud is less than 20%, and the specific surface area of the waste mud is 400-450m 2 / kg, the calcium content of the waste sludge is greater than 40%.
[0016] Preferably, the aspect ratio of the carbon fiber is 100-400:1, and the length of the carbon fiber is 1-3 cm; the aspect ratio of the steel fiber is 80-100:1, and the length of the steel fiber is 0.5-1.5 cm.
[0017] Preferably, the water reducing agent is a special water reducing agent for UHPC, and the water reducing rate of the water reducing agent is greater than 45%.
[0018] A method for preparing recycled aggregate comprises the following steps:
[0019] Step 1: weigh tailings, coal gangue, strong electrolyte, waste mud, carbon fiber and steel fiber according to mass fraction, mix them thoroughly, soak them for 24-36 hours, filter and dry them;
[0020] Step 2: Weigh the construction phosphogypsum, steel slag and carbide slag by mass, mix them thoroughly and remove fine powder through air separation;
[0021] Step 3, fully mixing the dried tailings, coal gangue, strong electrolyte, waste mud, carbon fiber and steel fiber with the de-powdered building phosphogypsum, steel slag and carbide slag, adding them to the weak electrolyte and water reducer weighed by mass, mixing them evenly and placing them in a granulator for granulation;
[0022] Step 4: Place the granulated particles into an autoclave and autoclave at 175-785°C for 7-10 hours to obtain recycled aggregate.
[0023] Preferably, in the step 2, the construction phosphogypsum, steel slag and carbide slag are fully mixed and then air-selected to obtain a fine powder content of 1-2%.
[0024] Preferably, in step three, the particle size obtained by granulation in the granulator is 25-35 mm.
[0025] The beneficial effects of this technical solution are as follows:
[0026] 1. The recycled aggregate provided by the present invention realizes precise stacking by controlling the particle grading, reduces the harmful pore content, and finely cements the material particles to reduce the total specific surface area of the material and reduce the water consumption. In addition, waste mud containing limestone is used to supplement the micropores. Limestone has a certain water-reducing effect, which can further increase the compactness of the system, reduce the water-cement ratio, and reduce the harmful pore content.
[0027] 2. The present invention provides a recycled aggregate, in which rich carbon fibers and steel fibers are integrated. The addition of these high-performance fibers not only significantly improves the strength of the aggregate itself, but also the fibers extending from the surface of the aggregate greatly enhance the connectivity with the surrounding interface, thereby further enhancing the overall structural strength of the concrete prepared from the aggregate, showing excellent performance and wide application potential; the waste mud contains a large amount of polyacrylamide, which can effectively assist the dispersion of the fibers and further increase the tensile properties of the fiber mesh; the holes in the coal gangue provide a fulcrum for the fibers inside the aggregate, thereby strengthening the friction between the fibers and the aggregate and enhancing the performance of the recycled aggregate.
[0028] 3. The present invention provides a recycled aggregate, wherein iron tailings, chalcopyrite tailings, strong electrolyte solvents, etc. all contain a large amount of polar materials, especially coal gangue, which contains a large number of large pores inside, and strong electrolyte solvents can enter and adhere to the inside. During the molding process, the cementitious material further fills the internal gaps of the coal gangue, effectively preventing the escape of electrolyte solutes. The prepared recycled aggregate has good polarity, while cement and river sand in concrete are non-polar materials. When heated by microwaves, only the polar material of the aggregate is heated and expanded, and the mortar in the concrete along the interface is dissociated to realize the regeneration of the aggregate, and there is no old mortar on the surface. The internal pores brought by the coal gangue will also enhance the aggregate's ability to absorb waves and improve the heating performance of the aggregate.
[0029] 4. The recycled aggregate provided by the present invention contains a large amount of conductive material, and the conductive performance is enhanced by carbon fiber and steel fiber, and the conductivity of the aggregate frame is realized by overlapping with other aggregates. The cement and river sand in the concrete are both insulating materials. When voltage is applied to the concrete, ions or electrons migrate in the aggregate frame to form current and generate heat. Only the aggregate expands due to heat, and the mortar in the concrete along the interface dissociates, thereby realizing the regeneration of the aggregate, and there is no old mortar on the surface.
[0030] 5. The present invention provides a recycled aggregate, which exhibits excellent solid waste utilization and significantly reduces production costs. It has high strength and is particularly good at bonding with concrete mortar. What is even more commendable is that the aggregate can be easily regenerated by electrical or microwave heating, demonstrating extremely high practical value and environmental benefits.
[0031] Sixth, the present invention provides a kind of recycled aggregate, strong electrolyte solvent improves the polarity and conductivity of materials such as coal gangue and tailings; if only weak electrolyte solvent is used to improve the overall polarity and conductivity of aggregate, too much electrolyte solute will cause excessive gas content in the gelling component, corrode steel bars, destroy internal crystallization, etc., affecting the performance of concrete, so the final amount of electrolyte solute added is strictly controlled in the preparation of aggregate; in addition, the substances mixed with the strong electrolyte solution are all ion conductive or non-gelling substances with poor polarity, which do not affect the performance of the gelling material after contact with the strong electrolyte and can improve the conductivity and polarity, balancing the internal conductivity and polarity of the aggregate material. The firmness of the recycled aggregate obtained by the present invention is less than 1.2%, the strength is greater than 120MPa, the crushing index is less than 2.6%, the water absorption rate is less than 0.15%, and the microwave heating efficiency is greater than 80℃; it can meet the requirements for aggregate use.
[0032] 7. The present invention provides a method for preparing a recycled aggregate. During the granulation process, the construction phosphogypsum is quickly hydrated, so that the particles can be formed according to the design plan. The sodium sulfate, potassium hydroxide, sodium hydroxide, ferric sulfate, etc. in the electrolyte solution in the system have a certain early strength effect and can help improve the early strength. In addition, steel slag, carbide slag, etc. can also be quickly hydrated under the combined action of alkali excitation and sulfate excitation, and together with the construction phosphogypsum, form early strength and complete the shaping.
[0033] 8. The present invention provides a method for preparing recycled aggregate, wherein the main materials are calcium or silicon, and the calcium-silicon ratio is controlled by the material composition; after shaping and autoclaving, the prepared aggregate has excellent compressive strength, easily exceeding 150MPa, showing excellent mechanical properties, and providing a reliable material basis for various high-strength applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 is a schematic diagram of the present invention;
[0035] Figure 2 It is a practical diagram of the present invention. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0037] Example
[0038] A recycled aggregate is made of the following raw materials in parts by weight: 40-50 parts of tailings, 2-5 parts of coal gangue, 5-10 parts of building phosphogypsum, 10-15 parts of strong electrolyte solvent, 4-6 parts of weak electrolyte solvent, 20-25 parts of steel slag, 5-8 parts of carbide slag, 1-3 parts of waste mud, 0.1-0.5 parts of carbon fiber, 2-4 parts of steel fiber and 0.5-1 part of water reducing agent.
[0039] Preferably, the tailings are one or more of iron tailings, graphite tailings, and copper tailings; the resistivity of the tailings is less than 1000 ohms, the fineness modulus of the tailings is 2.5-3.0, and the silicon content of the tailings is greater than 60%.
[0040] Preferably, the coal gangue is solid waste discharged during coal mining and coal washing, the particle size of the coal gangue is 0.1-2 mm, and the fineness modulus of the coal gangue is 3.3-3.5.
[0041] Preferably, the building phosphogypsum is obtained by heating and dehydrating solid waste phosphogypsum generated in the phosphoric acid production process, and its hemihydrate gypsum content is greater than 80%, and the 80um sieve residue is less than 10%.
[0042] Preferably, the strong electrolyte solvent is one or more of an aqueous solution of ferric sulfate, an aqueous solution of sodium sulfate, an aqueous solution of sodium hydroxide, and an aqueous solution of potassium hydroxide; and the mass fraction of the strong electrolyte solvent is 20-35wt%.
[0043] Preferably, the weak electrolyte solvent is one or more of an aqueous solution of ferric sulfate, an aqueous solution of sodium sulfate, an aqueous solution of sodium hydroxide, and an aqueous solution of potassium hydroxide; and the mass fraction of the weak electrolyte solvent is 2-5wt%.
[0044] Preferably, the calcium content of the steel slag is greater than 50%, and the specific surface area of the steel slag is 350-400m 2 / kg.
[0045] Preferably, the carbide slag is the main solid waste from carbide hydrolysis to produce acetylene gas, the calcium content of the carbide slag is greater than 80%, and the specific surface area of the carbide slag is 350-400m 2 / kg.
[0046] Preferably, the waste mud is solid waste from water washing and powder removal in the limestone machine-made sand production process, the water content of the waste mud is less than 20%, and the specific surface area of the waste mud is 400-450m 2 / kg, the calcium content of the waste sludge is greater than 40%.
[0047] Preferably, the aspect ratio of the carbon fiber is 100-400:1, and the length of the carbon fiber is 1-3 cm; the aspect ratio of the steel fiber is 80-100:1, and the length of the steel fiber is 0.5-1.5 cm.
[0048] Preferably, the water reducing agent is a special water reducing agent for UHPC, and the water reducing rate of the water reducing agent is greater than 45%.
[0049] A method for preparing recycled aggregate comprises the following steps:
[0050] Step 1: weigh tailings, coal gangue, strong electrolyte, waste mud, carbon fiber and steel fiber according to mass fraction, mix them thoroughly, soak them for 24-36 hours, filter and dry them;
[0051] Step 2: Weigh the construction phosphogypsum, steel slag and carbide slag by mass, mix them thoroughly and remove fine powder through air separation;
[0052] Step 3, fully mixing the dried tailings, coal gangue, strong electrolyte, waste mud, carbon fiber and steel fiber with the de-powdered building phosphogypsum, steel slag and carbide slag, adding them to the weak electrolyte and water reducer weighed by mass, mixing them evenly and placing them in a granulator for granulation;
[0053] Step 4: Put the granulated particles into an autoclave and autoclave at 175-785°C for 7-10 hours to obtain recycled aggregate (such as Figure 1 and Figure 2 shown).
[0054] The proportion of recycled aggregate in each embodiment is shown in Table 1:
[0055] Table 1 Recycled aggregate raw materials of each embodiment
[0056]
[0057]
[0058] The parameter requirements of each raw material in the recycled aggregate of each embodiment are shown in Table 2:
[0059] Table 2 Parameter requirements of each raw material in the recycled aggregate of each embodiment
[0060]
[0061]
[0062] The preparation methods of recycled aggregates in various embodiments are shown in Table 3:
[0063] Table 3 Parameter requirements of the recycled aggregate preparation method in each embodiment
[0064]
[0065]
[0066] The recycled aggregate prepared in the above example was tested for relevant properties of the recycled aggregate with reference to the national standard GB / T 14685-2022 "Pebbles and crushed stones for construction", and the aggregate was placed flat in a 100*100*100mm non-polar mold, and the mold was placed in a KQ6000 adjustable industrial box-type microwave heating device with a power of 20kW and a frequency of 2.45GHz. The temperature was recorded after heating for ten minutes to test the microwave heating efficiency. The results are shown in Table 4:
[0067] Table 4 Performance parameters of recycled aggregates in various examples
[0068]
[0069] Comparative Example 1
[0070] The difference between this comparative example and Example 1 is that the tailings are 35g; the recycled aggregate is prepared, and the firmness of the recycled aggregate is 0.9%, the strength is 117MPa, the crushing index is 2.6%, the water absorption rate is 0.13%, and the microwave heating efficiency is 101.3°C.
[0071] Comparative Example 2
[0072] The difference between this comparative example and Example 1 is that the tailings are 55g; the recycled aggregate is prepared, and the firmness of the recycled aggregate is 1.3%, the strength is 125MPa, the crushing index is 2.3%, the water absorption rate is 0.08%, and the microwave heating efficiency is 95.1°C.
[0073] Comparative Example 3
[0074] The difference between this comparative example and Example 1 is that the resistivity of the tailings is 1050 ohms; the recycled aggregate is prepared, and the firmness of the recycled aggregate is 1.1%, the strength is 122 MPa, the crushing index is 2.5%, the water absorption rate is 0.1%, and the microwave heating efficiency is 96.8°C.
[0075] Comparative Example 4
[0076] The difference between this comparative example and Example 1 is that the fineness modulus of the tailings is 3.0; the recycled aggregate is prepared, and the firmness of the recycled aggregate is 1.3%, the strength is 105 MPa, the crushing index is 2.8%, the water absorption rate is 0.15%, and the microwave heating efficiency is 103.2°C.
[0077] Comparative Example 5
[0078] The difference between this comparative example and Example 1 is that the silicon content of the tailings is 75%; the recycled aggregate is prepared, and the firmness of the recycled aggregate is 1.8%, the strength is 98.6 MPa, the crushing index is 2.9%, the water absorption rate is 0.18%, and the microwave heating efficiency is 101.6°C.
[0079] Comparative Example 6
[0080] The difference between this comparative example and Example 1 is that no strong electrolyte solvent is used; the recycled aggregate is prepared, and the solidity of the recycled aggregate is 1.2%, the strength is 112 MPa, the crushing index is 2.7%, the water absorption rate is 0.13%, and the microwave heating efficiency is 94.9°C.
[0081] Comparative Example 7
[0082] The difference between this comparative example and Example 1 is that the calcium content of the steel slag is 45%, and the specific surface area is 320m 2 / kg; the recycled aggregate was prepared, and the firmness of the recycled aggregate was 1.9%, the strength was 93.4MPa, the crushing index was 3.0%, the water absorption rate was 0.2%, and the microwave heating efficiency was 101.8℃.
[0083] Comparative Example 8
[0084] The difference between this comparative example and Example 1 is that the specific surface area of the steel slag is 420m 2 / kg; the recycled aggregate was prepared, and the firmness of the recycled aggregate was 2.6%, the strength was 81.3MPa, the crushing index was 3.5%, the water absorption rate was 0.29%, and the microwave heating efficiency was 99.1°C.
[0085] Comparative Example 9
[0086] The difference between this comparative example and Example 1 is that the calcium content of the carbide slag is 75%, and the specific surface area is 320m 2 / kg; the recycled aggregate was prepared, and the firmness of the recycled aggregate was 1.8%, the strength was 97.1MPa, the crushing index was 2.9%, the water absorption rate was 0.18%, and the microwave heating efficiency was 100.2℃.
[0087] Comparative Example 10
[0088] The difference between this comparative example and Example 1 is that the specific surface area of carbide slag is 420m 2 / kg; the recycled aggregate was prepared, and the firmness of the recycled aggregate was 2.3%, the strength was 93.4MPa, the crushing index was 2.8%, the water absorption rate was 0.16%, and the microwave heating efficiency was 99.4℃.
[0089] Comparative Example 11
[0090] The difference between this comparative example and Example 1 is that no carbon fiber is used; the recycled aggregate is prepared, and the firmness of the recycled aggregate is 1.2%, the strength is 115 MPa, the crushing index is 2.6%, the water absorption rate is 0.11%, and the microwave heating efficiency is 94.7°C.
[0091] Comparative Example 12
[0092] The difference between this comparative example and Example 1 is that no steel fiber is used; the recycled aggregate is prepared, and the solidity of the recycled aggregate is 1.1%, the strength is 109 MPa, the crushing index is 2.8%, the water absorption rate is 0.12%, and the microwave heating efficiency is 95.1°C.
[0093] Comparative Example 13
[0094] The difference between this comparative example and Example 1 is that no weak electrolyte solvent is used, the firmness of the recycled aggregate is 1.5%, the strength is 97 MPa, the crushing index is 2.8%, the water absorption rate is 0.15%, and the microwave heating efficiency is 61.1°C.
[0095] Comparative Example 14
[0096] The difference between this comparative example and Example 1 is that the content of fine powder is 0.5%, the firmness of the recycled aggregate is 1.8%, the strength is 76 MPa, the crushing index is 3.1%, the water absorption rate is 0.19%, and the microwave heating efficiency is 95.7°C.
[0097] Comparative Example 15
[0098] The difference between this comparative example and Example 1 is that the content of fine powder is 2.5%, the firmness of the recycled aggregate is 2.3%, the strength is 51 MPa, the crushing index is 3.6%, the water absorption rate is 0.24%, and the microwave heating efficiency is 91.8°C.
[0099] Comparative Example 16
[0100] The difference between this comparative example and Example 1 is that the particle size obtained by granulation is 20 mm, the firmness of the recycled aggregate is 1.3%, the strength is 98 MPa, the crushing index is 2.8%, the water absorption rate is 0.13%, and the microwave heating efficiency is 106.3°C.
[0101] Comparative Example 17
[0102] The difference between this comparative example and Example 1 is that the particle size obtained by granulation is 40 mm, the firmness of the recycled aggregate is 0.8%, the strength is 133 MPa, the crushing index is 2.2%, the water absorption rate is 0.9%, and the microwave heating efficiency is 79.2°C.
[0103] As can be seen from the above, when the tailings are too low, the strength and crushing index of Comparative Example 1 are significantly reduced compared with Example 1; when the tailings are too high, the firmness is reduced in Comparative Example 2; when the fineness modulus of the tailings is too low, the firmness, strength and crushing index of Comparative Example 4 are significantly reduced compared with Example 1; when the silicon content of the tailings is too low, the firmness, strength, crushing index and water absorption rate of Comparative Example 5 are significantly reduced compared with Example 1; when only the local cut-off solvent is used, the firmness, strength and crushing index of Comparative Example 6 are significantly reduced compared with Example 1; when the calcium content and specific surface area of the steel slag are too low, the firmness, strength, crushing index and water absorption rate of Comparative Example 7 are significantly reduced compared with Example 1; when the specific surface area of the steel slag is too high, the firmness, strength, crushing index and water absorption rate of Comparative Example 8 are significantly reduced compared with Example 1; when the calcium content and specific surface area of the carbide slag are too low, the firmness, strength, crushing index and water absorption rate of Comparative Example 9 are significantly reduced compared with Example 1; Compared with Example 1, when the specific surface area of carbide slag is too high, the firmness, strength, crushing index and water absorption rate are significantly reduced; Compared with Example 1, when carbon fiber is not used, the firmness, strength and crushing index of Comparative Example 11 are significantly reduced; Compared with Example 1, when steel fiber is not used, the strength and crushing index are significantly reduced; Compared with Example 1, when a weak electrolyte solvent is not used, the firmness, strength, crushing index, water absorption rate and microwave heating efficiency are significantly reduced; Compared with Example 1, when the content of fine powder is too low, the firmness, strength, crushing index and water absorption rate are significantly reduced; Compared with Example 1, when the content of fine powder is too high, the firmness, strength, crushing index and water absorption rate are significantly reduced; Compared with Example 1, when the particle size obtained by granulation is too small, the firmness, strength and crushing index are significantly reduced; Compared with Example 1, when the particle size obtained by granulation is too large, the microwave heating efficiency is significantly reduced.
[0104] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A recycled aggregate, characterized in that: The invention is made of the following raw materials in parts by weight: 40-50 parts of tailings, 2-5 parts of coal gangue, 5-10 parts of building phosphogypsum, 10-15 parts of strong electrolyte solvent, 4-6 parts of weak electrolyte solvent, 20-25 parts of steel slag, 5-8 parts of carbide slag, 1-3 parts of waste mud, 0.1-0.5 parts of carbon fiber, 2-4 parts of steel fiber and 0.5-1 parts of water reducing agent.
2. The recycled aggregate according to claim 1, characterized in that: The tailings are one or more of iron tailings, graphite tailings, and copper tailings; the resistivity of the tailings is less than 1000 ohms, the fineness modulus of the tailings is 2.5-3.0, and the silicon content of the tailings is greater than 60%.
3. The recycled aggregate according to claim 1, characterized in that: The coal gangue is solid waste discharged during the coal mining process and the coal washing process. The particle size of the coal gangue is 0.1-2 mm, and the fineness modulus of the coal gangue is 3.3-3.
5.
4. The recycled aggregate according to claim 1, characterized in that: The building phosphogypsum is obtained by heating and dehydrating the solid waste phosphogypsum generated in the phosphoric acid production process, and its hemihydrate gypsum content is greater than 80%, and the 80um sieve residue is less than 10%.
5. The recycled aggregate according to claim 1, characterized in that: The strong electrolyte solvent is one or more of an aqueous solution of ferric sulfate, an aqueous solution of sodium sulfate, an aqueous solution of sodium hydroxide, and an aqueous solution of potassium hydroxide; and the mass fraction of the strong electrolyte solvent is 20-35wt%.
6. The recycled aggregate according to claim 1, characterized in that: The weak electrolyte solvent is one or more of an aqueous solution of ferric sulfate, an aqueous solution of sodium sulfate, an aqueous solution of sodium hydroxide, and an aqueous solution of potassium hydroxide; and the mass fraction of the weak electrolyte solvent is 2-5wt%.
7. The recycled aggregate according to claim 1, characterized in that: The calcium content of the steel slag is greater than 50%, and the specific surface area of the steel slag is 350-400m 2 / kg.
8. The recycled aggregate according to claim 1, characterized in that: The carbide slag is the main solid waste from carbide hydrolysis to produce acetylene gas. The calcium content of the carbide slag is greater than 80%, and the specific surface area of the carbide slag is 350-400m 2 / kg.
9. The recycled aggregate according to claim 1, characterized in that: The waste mud is the sedimentation solid waste from water washing and powder removal in the limestone machine-made sand production process. The water content of the waste mud is less than 20%, and the specific surface area of the waste mud is 400-450m 2 / kg, the calcium content of the waste sludge is greater than 40%.
10. The recycled aggregate according to claim 1, characterized in that: The aspect ratio of the carbon fiber is 100-400:1, and the length of the carbon fiber is 1-3 cm; the aspect ratio of the steel fiber is 80-100:1, and the length of the steel fiber is 0.5-1.5 cm.
11. The recycled aggregate according to claim 1, characterized in that: The water reducing agent is a special water reducing agent for UHPC, and the water reducing rate of the water reducing agent is greater than 45%.
12. A method for preparing recycled aggregate according to any one of claims 1 to 11, characterized in that: The following steps are involved: Step 1: weigh tailings, coal gangue, strong electrolyte, waste mud, carbon fiber and steel fiber according to mass fraction, mix them thoroughly, soak them for 24-36 hours, filter and dry them; Step 2: Weigh the construction phosphogypsum, steel slag and carbide slag by mass, mix them thoroughly and remove fine powder through air separation; Step 3, fully mixing the dried tailings, coal gangue, strong electrolyte, waste mud, carbon fiber and steel fiber with the de-powdered building phosphogypsum, steel slag and carbide slag, adding them to the weak electrolyte and water reducer weighed by mass, mixing them evenly and placing them in a granulator for granulation; Step 4: Place the granulated particles into an autoclave and autoclave at 175-785°C for 7-10 hours to obtain recycled aggregate.
13. The method for preparing recycled aggregate according to claim 12, characterized in that: In the step 2, the construction phosphogypsum, steel slag and carbide slag are fully mixed and then air-selected to obtain a fine powder content of 1-2%.
14. The method for preparing recycled aggregate according to claim 13, characterized in that: In the step 3, the particle size obtained by granulation in the granulator is 25-35 mm.
Citation Information
Patent Citations
Modified recycled coarse aggregate and method for preparing recycled concrete using modified recycled coarse aggregate
CN109265038A
Multi-element solid waste recycled aggregate and preparation process thereof
CN113149586A
Freeze-thaw-resistant foam concrete for high-cold and high-altitude areas and preparation method thereof
CN113698144A
Process for preparing recycled aggregate from non-flow silicate concrete waste
CN116768562A
Lightweight solid waste porous aggregate as well as preparation method and application thereof
CN117550913A